2017
DOI: 10.3389/fimmu.2017.00212
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells: Uncertain Allies against Malaria

Abstract: Until recently, studies of natural killer (NK) cells in infection have focused almost entirely on their role in viral infections. However, there is an increasing awareness of the potential for NK cells to contribute to the control of a wider range of pathogens, including intracellular parasites such as Plasmodium spp. Given the high prevalence of parasitic diseases in the developing world and the devastating effects these pathogens have on large numbers of vulnerable people, investigating interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 156 publications
(238 reference statements)
1
86
0
Order By: Relevance
“…Earlier studies have described direct lysis of iRBCs by NK cells in the 60 absence of Abs or Ab-dependent inhibition of P. falciparum growth by NK cells (Mavoungou,61 Luty, & Kremsner, 2003; Orago & Facer, 1991). However, other studies have not confirmed such 62 results (Wolf et al, 2017). Here, we present a detailed study of the activity of primary, 63 unstimulated human NK cells mixed with RBCs, infected or not by P.f., and evaluate the NK cell 64 responses using several different quantitative assays.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Earlier studies have described direct lysis of iRBCs by NK cells in the 60 absence of Abs or Ab-dependent inhibition of P. falciparum growth by NK cells (Mavoungou,61 Luty, & Kremsner, 2003; Orago & Facer, 1991). However, other studies have not confirmed such 62 results (Wolf et al, 2017). Here, we present a detailed study of the activity of primary, 63 unstimulated human NK cells mixed with RBCs, infected or not by P.f., and evaluate the NK cell 64 responses using several different quantitative assays.…”
mentioning
confidence: 83%
“…Previous work has shown that IL-2 produced by T cells following malaria infection or injection 306 of a malaria vaccine activates IFN-g production by NK cells (Wolf et al, 2017). In addition, P.f.…”
Section: Selective Lysis Of Pf-infected Rbcs By Primary Nk Cells Inmentioning
confidence: 98%
“…Natural killer (NK) cells are activated by cytokines (IL12, IL15 and IL18) secreted by monocytes/macrophages and DCs during infection, and experiments demonstrating their direct cytotoxic killing of parasitized‐RBCs have been reviewed in detail elsewhere . NK cell production of pro‐inflammatory cytokines, such as IFNγ also contribute to the immunopathology associated with malaria .…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…The role of NK cells in natural immunity or vaccine‐induced protection against malaria infection remains to be established . NK cell activation has been described to varying degrees in different experimental murine models and NK cells have been shown to contribute directly to the elimination of Plasmodium falciparum ‐infected red blood cells (RBC) in a humanised mouse model .…”
Section: Malariamentioning
confidence: 99%
“…The role of NK cells in natural immunity or vaccine-induced protection against malaria infection remains to be established. 89 NK cell activation has been described to varying degrees in different experimental murine models 90,91 and NK cells have been shown to contribute directly to the elimination of Plasmodium falciparuminfected red blood cells (RBC) in a humanised mouse model. 92 In vitro studies of human PBMC show NK cells are readily activated by P. falciparum-infected RBC; the resulting NK cell proliferation, IFN-c production, CD25 and CD69 expression were further demonstrated to be dependent on IL-2 and accessory cell IL-12 and IL-18 production and on cell-cell contact.…”
Section: Malariamentioning
confidence: 99%